2017
DOI: 10.1530/ec-17-0207
|View full text |Cite
|
Sign up to set email alerts
|

MEN1 gene mutation with parathyroid carcinoma: first report of a familial case

Abstract: BackgroundThe occurrence of parathyroid carcinoma in multiple endocrine neoplasia type I (MENI) is rare and the 15 cases of malignant parathyroid tumor reported so far have been associated with MENI in individuals and not with multiple members within a family.MethodsWe report on a 61-year-old male, operated for a 7.3 cm parathyroid carcinoma infiltrating the esophagus. In his brother, a 4.6 cm parathyroid carcinoma was diagnosed histologically, while in the daughter, neck ultrasonography revealed 2 extrathyroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 25 publications
0
14
0
1
Order By: Relevance
“…Herein, one patient with AA presented with familial MEN1 syndrome characterized by AA and pituitary [30], and to date, only three cases of AA have been associated with MEN1 syndrome; two carried pathogenic variants of MEN1 [31][32][33]. MEN1 primary hyperparathyroidism is now well established owing to its role in benign parathyroid lesions or PA. Two wholeexome capture and high-throughput sequencing studies of PA revealed MEN1 alterations as a major driver, with an alteration frequency of 35% [13,14], and mutations of the gene have also been identified in AA and PC [34,35]. In this study, the MEN1 mutation occurred at a rate of 8% in PA, whereas no such alterations were detected in PC or AA.…”
Section: Discussionmentioning
confidence: 51%
“…Herein, one patient with AA presented with familial MEN1 syndrome characterized by AA and pituitary [30], and to date, only three cases of AA have been associated with MEN1 syndrome; two carried pathogenic variants of MEN1 [31][32][33]. MEN1 primary hyperparathyroidism is now well established owing to its role in benign parathyroid lesions or PA. Two wholeexome capture and high-throughput sequencing studies of PA revealed MEN1 alterations as a major driver, with an alteration frequency of 35% [13,14], and mutations of the gene have also been identified in AA and PC [34,35]. In this study, the MEN1 mutation occurred at a rate of 8% in PA, whereas no such alterations were detected in PC or AA.…”
Section: Discussionmentioning
confidence: 51%
“…This mutation is predicted to significantly decrease the protein stability of MENIN by targeting the protein for degradation [ 79 ]. The D423N mutant (D418N in isoform 2) is also exclusively found in parathyroid cancers [ 80 , 81 ]. The molecular consequence of this mutation is unexplored.…”
Section: Resultsmentioning
confidence: 99%
“…4,5 Advances in the molecular understanding of PC have described some frequent genomic alterations in PC, including in genes such as CDC73, CCND1, RB, MEN1, RET and TP53. [6][7][8][9][10][11] The major morbidity of PC usually results from intractable hypercalcemia induced by inoperable recurrent or metastatic lesions. The diagnosis of PC can be challenging, as most of the histopathologic features of PC can also be found in atypical parathyroid adenoma, unless an invasive growth pattern or distant metastases are clinically evident.…”
Section: Introductionmentioning
confidence: 99%